Daya Terima, Zat Gizi, dan Nilai Energi Roti Tawar Anti- Diabetes dengan Penambahan Sari Mengkudu (Morinda citrifolia L.) - Rista Anggriani; Nurul Laelatunisa; Nikmatul Rizky; Rachmadhanti Arum (Universitas Muhammadiyah Malang, 2020)
White bread is a popular food product in Indonesia which is dominated by carbohydrate content. To improve its function, the noni juice which has phytochemical compounds of the alkaloid group was added. However, noni has a very strong aroma, which makes this noni rarely processed. This study aims to analyze the nutritional content, energy value, and organoleptic test of white bread added with noni juice. This research used a descriptive experimental design that the data is compared with SNI No 01-3840-1995 of white bread (Standard Nasional Indonesia = Indonesia Standard Requirement). Noni juice is added by four levels (0, 50, 150, 250ml). The results found that the more noni juice added would cause the addition of flour used, thereby increasing the calories per serving. In addition, the addition of noni juice causes an increase in brown color and aroma but decreases the tenderness, and sweetness of white bread.